The Foundations of AI-Driven Arabic Learning Materials: Toward an Integrative Conceptual Framework - Imam Haromaen; Vina Ri’ayatillah; Adi Fadli; Dewi Qotrun Nada Najwa (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2026)
Artificial Intelligence (AI) has created new opportunities for developing Arabic learning materials that are more adaptive, personalized, and interactive. However, existing studies have primarily focused on technological applications, with limited attention to the theoretical foundations that should guide the development of AI-driven Arabic learning materials. This study aims to analyze the theoretical foundations underlying the development of Arabic learning materials in the era of artificial intelligence. Using a qualitative library research design, data were collected from scholarly books, journal articles, conference proceedings, and other relevant academic publications. The data were analyzed through content analysis, thematic analysis, and conceptual synthesis. The findings indicate that the development of AI-driven Arabic learning materials should be grounded in five interconnected foundations: philosophical, pedagogical, linguistic, psychological, and sociocultural. These foundations provide a comprehensive framework for integrating AI into Arabic language education while ensuring adaptability, personalization, interactivity, and cultural authenticity. This study contributes an integrative conceptual perspective that positions AI as an educational enabler rather than merely a technological tool.